2022
DOI: 10.3390/ijerph192315607
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Activity of Daily Living Status of the Older Adults and Its Influencing Factors: A Cross-Sectional Study

Abstract: This study aimed to explore the impaired activity of the daily living ability status and its influencing factors among older adults. A sample of 10,148 participants (≥60 years old) who met the requirements for the activity of daily living scale was used in this study, and the Health and Aging Tracking Survey was selected for data collection. The impaired activities of the daily living status of older adults and their influencing factors were analyzed by single-factor descriptive analysis and multi-factor logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In the entire population of elderly patients we examined, data analysis showed that an increase in independence and autonomy in activities of daily living was directly related to a growth in strength. This result is consistent with previous studies in the literature that have linked health to hand strength [57,58]. Furthermore, several studies show that poor muscle strength is associated with cognitive decline, low quality of life, and depressive symptoms in elderly patients [59,60].…”
Section: Discussionsupporting
confidence: 92%
“…In the entire population of elderly patients we examined, data analysis showed that an increase in independence and autonomy in activities of daily living was directly related to a growth in strength. This result is consistent with previous studies in the literature that have linked health to hand strength [57,58]. Furthermore, several studies show that poor muscle strength is associated with cognitive decline, low quality of life, and depressive symptoms in elderly patients [59,60].…”
Section: Discussionsupporting
confidence: 92%
“…Post-pandemic, some participants struggled to be as sociable and physically active as they were in pre-pandemic times due to getting used to staying home and feeling little to no reason to meet people outside. While a gradual reduction of activities of daily living is a typical process as one ages, 34 this does not fully explain the stark difference in socialising in pre-and post-pandemic times. One possible reason for this difference is the long-term deficits that have been found in older adult COVID-19 survivors due to the cognitive and physical changes brought about by the virus.…”
Section: Discussionmentioning
confidence: 97%